2020
DOI: 10.31234/osf.io/nkvap
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why not both? Rethinking categorical and continuous approaches to bilingualism

Abstract: Bilingualism is a complex construct, and it can be difficult to define and model. This paper proposes that the field of bilingualism can draw from other fields of psychology, by integrating advanced psychometric models that incorporate both categorical and continuous properties. These models can unify the widespread use of bilingual and monolingual groups that exist in the literature with recent proposals that bilingualism should be viewed as a continuous variable. In the paper, we highlight two models of pote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Third, although there is a movement toward treating bilingualism as a continuous variable that is endorsed by many (e.g., Champoux-Larsson & Dylman, 2019;DeLuca et al, 2019;Edwards, 2012;Gullifer et al, 2018;Gullifer & Titone, 2020;Incera & McLennan, 2018;Jylkkä et al, 2017;Kaushanskaya & Prior, 2015;Luk & Bialystok, 2013;Sulpizio et al, 2020;Surrain & Luk, 2019), as Kremin and Byers-Heinlein (2020) point out, there are situations where this may not be possible or preferable (e.g., with small samples). Therefore, giving up a dichotomous classification of bilingualism altogether may not be the answer when it comes to operationalizing bilingualism (Kremin & Byers-Heinlein, 2020). Using a factor mixture model or a grade-of-membership model, which allow for categorization but considers the variation within the categories, would allow analysing results based on categories, on a continuous scale, or even on both (Kremin & Byers-Heinlein, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, although there is a movement toward treating bilingualism as a continuous variable that is endorsed by many (e.g., Champoux-Larsson & Dylman, 2019;DeLuca et al, 2019;Edwards, 2012;Gullifer et al, 2018;Gullifer & Titone, 2020;Incera & McLennan, 2018;Jylkkä et al, 2017;Kaushanskaya & Prior, 2015;Luk & Bialystok, 2013;Sulpizio et al, 2020;Surrain & Luk, 2019), as Kremin and Byers-Heinlein (2020) point out, there are situations where this may not be possible or preferable (e.g., with small samples). Therefore, giving up a dichotomous classification of bilingualism altogether may not be the answer when it comes to operationalizing bilingualism (Kremin & Byers-Heinlein, 2020). Using a factor mixture model or a grade-of-membership model, which allow for categorization but considers the variation within the categories, would allow analysing results based on categories, on a continuous scale, or even on both (Kremin & Byers-Heinlein, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, giving up a dichotomous classification of bilingualism altogether may not be the answer when it comes to operationalizing bilingualism (Kremin & Byers-Heinlein, 2020). Using a factor mixture model or a grade-of-membership model, which allow for categorization but considers the variation within the categories, would allow analysing results based on categories, on a continuous scale, or even on both (Kremin & Byers-Heinlein, 2020). The flexibility that such models provide would allow choosing an approach that would be driven by the research question, by the latent concept that is analyzed, and by the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our aim is not to argue for or against the use of composite measures -such as language entropy (Gullifer & Titone, 2020) or the continuous factor score method advocated by Anderson et al (2018). Furthermore, while acknowledging the multi-dimensional nature of bilingualism, our purpose is not to discuss the relative importance of each dimensionsuch as language proficiency (Hulstijn, 2012) or child-level and context-level variables (Byers-Heinlein, Esposito, et al, 2019), nor to argue about the relative merits or the comparability of categorical vs. continuous approaches to bilingualism (Kremin & Byers-Heinlein, 2020). Rather, we will focus on the raw measures used to operationalise bilingualism in order to:…”
Section: Introductionmentioning
confidence: 99%
“…Some recent opinion papers have tried to provide reasons for the conflicting results and suggested that diverging approaches to the multidimensional nature of bilingualism might be partly responsible for the lack of replicability in findings (Valian, 2015;Bak, 2016). Marian and Hayakawa (2020) and Kremin and Byers-Heinlein (2020) have convincingly argued that bilingualism research would benefit from greater transparency regarding the measures used to operationalise the variables of interest.…”
Section: Introductionmentioning
confidence: 99%